The Moderating Effects from Corporate Governance Characteristics on the Relationship Between Available Slack and Community-Based Firm Performance - Harrison, Jeffrey S.; Coombs, Joseph E. 1966- (2012)
Recent perspectives on community investments suggest that they are opportunities for firms to create value for shareholders and other stakeholders. However, many corporate managers are still influenced by a widely held belief that such investments erode profits and are therefore unjustifiable from an agency perspective. In this paper, we refine and test theory regarding countervailing forces that influence community-based firm performance. We hypothesize that high levels of available slack will be associated with higher community-based performance, but that this relationship will be moderated by three important governance variables: board independence, investment fund ownership, and CEO ownership. We find support for our hypotheses in longitudinal study of a large sample of U.S. corporations.
Keywords: Stakeholder Theory; Organizational slack; Corporate Governance; Community-based performance; Agency Theory